Identification of metabolites of dalfampridine (4-aminopyridine) in human subjects and reaction phenotyping of relevant cytochrome P450 pathways. (29th August 2013) - Caggiano, Anthony; Blight, Andrew
Abstract: Objectives: An extended release formulation of dalfampridine (4-aminopyridine; 4-AP), a potassium channel blocker is available in the USA to improve walking in patients with multiple sclerosis. This study investigated the human metabolites of 4-AP and the cytochrome P450 (CYP450) pathways responsible for 4-AP metabolism. Methods: Metabolites were identified, using thin layer chromatography, high performance liquid chromatography, and gas chromatography/mass spectroscopy, in plasma and urine samples obtained during an excretion balance study of four subjects who were administered a single oral 15-mg dose of 14 C-4-AP. Samples were compared with authentic standards of 4-AP, 2-hydroxy-4AP, 3-hydroxy-4AP, and 4-AP-N-oxide. Reaction phenotyping was performed in vitro using human liver microsomes and recombinant CYP450 enzymes with incubation in the presence of direct and time-dependent inhibitors to determine the CYP450 pathways involved in metabolite formation. Results: While most (∼70%) of the radioactivity detected in plasma at each time point corresponded to unchanged 4-AP, two major metabolites were recovered. One metabolite co-localized with the authentic reference standard of 3-hydroxy-4-AP, and the other metabolite was identified as the sulfate conjugate of 3-hydroxy-4-AP. Two minor components were observed, one accounting for 2% of radioactivity and the other below the level of quantitation. Reaction phenotyping showed moderate correlations for conversion of 4-AP to 3-hydroxy-4AP with both CYP2E1 ( r = 0.596; p < 0.001) and CYP2C8 ( r = 0.608; p < 0.001). Use of a CYP2E1 metabolism-dependent inhibitor inhibited formation of 3-hydroxy-4-AP with and without pre-incubation (higher inhibition with pre-incubation), further supporting the likelihood of CYP2E1 as a metabolic pathway. The main limitation of this study was the inability to identify the CYP enzymes responsible for the 3-hydroxylation of 4-AP, although this conversion represents only a minor metabolic pathway. Conclusion: There is limited metabolism of 4-AP in humans. The two major metabolites were 3-hydroxy-4-AP and 3-hydroxy-4-AP sulfate, likely through CYP2E1 pathways; the possibility of other CYP enzymes playing a minor role in 4-AP metabolism could not be established unequivocally. Overall, these data suggest that there is a low risk for drug–drug interactions via an impact on 4-AP metabolism through cytochrome pathways.